2012
DOI: 10.4314/ijbcs.v5i6.13
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation de la biométhanisation des effluents de manioc issus de la filière de fabrication de l’attiéké (semoule de manioc)

Abstract: Cette étude s'est penchée sur les conditions optimales de biodigestion des effluents de manioc de la filière attiéké (semoule de manioc). Ces effluents proviennent de la fabrique d'attiéké d'Azito (village Ebrié de la commune de Yopougon dans le district d'Abidjan). Les six digesteurs expérimentaux utilisés, ont été alimentés comme suit : 1) effluent de manioc ; 2) effluent + bouse de vache ; 3) effluent + urine ; 4-5 et 6) effluent + urine + différentes quantités de bouse de vache. Aux résultats, les digesteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For pH, analysis of the results obtained for the two types of digestates shows an average of 8.29 for E + U and 8.14 for E + U + C. These values could be explained by the desorption of proteins or the volatilization of acidic compounds or CO 2 during anaerobic digestion, as noted by [12] and [20]. These observations were also reported by [21] during their studies on the qualitative characterization of a liquid avicolic digestates derived from industrial biomethanization and use in fertigation of tomato plants.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…For pH, analysis of the results obtained for the two types of digestates shows an average of 8.29 for E + U and 8.14 for E + U + C. These values could be explained by the desorption of proteins or the volatilization of acidic compounds or CO 2 during anaerobic digestion, as noted by [12] and [20]. These observations were also reported by [21] during their studies on the qualitative characterization of a liquid avicolic digestates derived from industrial biomethanization and use in fertigation of tomato plants.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, new agricultural production policies encourage green agriculture. The reuse of residues or digests obtained after anaerobic digestion is stable, deodorized, largely free of pathogens and is rich in nitrogen compounds [8] [11] [12]. This digestate can be used as an amendment or biofertilizer [13] [14] for green and sustainable agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, despite the simple treatment of the experiments, the respective yields were highly important (115.01-189.16 L biogas/Kg VS; 67.97-130.89 L CH4 /Kg VS) compared to previous data of Nikiema et al, (2020, 2021) (16.55-40.04 L biogas/Kg VS and28.76-77.40 L CH4/Kg VS). Many studies showed the biogas production potential of agricultural, industrial, slaughterhouse, municipal wastes by anaerobic co-digestion or direct digestion (Kpata-Konan et al, 2011;Nikiema et al, 2015;Traoré et al, 2016;Sumardiono et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effluents from cassava pressing are very acidic (Mahan, 2004;Kpata, 2005;Kpata-Konan et al, 2011) with pH below 4. The acidity of raw sewage digesters observed before feeding would be partly due to the fermentation step conducted during the attiéké manufacturing process.…”
Section: Discussionmentioning
confidence: 99%
“…However, attiéké manufacturing process generates toxic effluents due to the high content of cassava cyanide up to 500 ppm (Asiedu, 1991 ;Chuzel et al, 1995 ;Ihedioha, 2002 ;Goualo et al, 2007). These effluents are highly loaded with organic matter with COD values ranging from 6 to 50 g/L and BOD ranging from 1.5 to 35 g/L (Chuzel et al, 1995 ;Marache, 2001 ;Mahan, 2004 ;Kpata, 2005 ;Ubalua, 2007 ;Kpata-Konan et al, 2011). Untreated and directly discharged into the nature, these effluents represent a major source of pollution for the receiving environment.…”
Section: Introductionmentioning
confidence: 99%